CORPUS LINGUISTICS, LANGUAGE CORPORA AND LANGUAGE TEACHING - Eska Perdana Prasetya; Anita Dewi Ekawati; Deni Sapta Nugraha; Ahmad Marzuq; Tiara Saputri Darlis (ENGLISH, 2020)
This research is about Corpus Linguistics, Language Corpora, And Language Teaching. As we know about this science is relatively new and is associated with technology. There are several areas discussed in this study such as several important parts of the corpus, the information generated in the corpus, four main characteristics of the corpus, Types of Corpora, Corpora in Language Teaching, several types that could be related to corpus research, Applications of corpus linguistics to language teaching may be direct or indirect. The field of applied linguistics analyses large collections of written and spoken texts, which have been carefully designed to represent specific domains of language use, such as informal speech or academic writing.